2016
DOI: 10.1186/s12985-016-0499-1
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus infection in chicken embryonic fibroblasts but not duck embryonic fibroblasts is associated with elevated host innate immune response

Abstract: BackgroundChickens and ducks are major hosts of Newcastle disease virus (NDV) with distinct responses to infection. However, whereas ducks are generally asymptomatic or exhibit only mild symptoms following NDV infection and are thus regarded as potential long-term reservoirs of the virus, chickens exhibit severe clinical lesions, transient infections and even death due to NDV infection. These differences may in part result from the host innate immune response to NDV infection.MethodsTo better understand the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
6
34
1
1
Order By: Relevance
“…The expressions of crucial genes, including TLR3, TLR7, IL1B, IRF7, IL8, STAT1, and MHC class I and II molecules, are characteristic of NDV infection in chicken cells. However, in previously performed studies, a significant expression of type I IFNs (INF-α and IFN-β) was observed against NDV infection [53,54]. Surprisingly, in our experimental settings, we were unable to observe this response.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…The expressions of crucial genes, including TLR3, TLR7, IL1B, IRF7, IL8, STAT1, and MHC class I and II molecules, are characteristic of NDV infection in chicken cells. However, in previously performed studies, a significant expression of type I IFNs (INF-α and IFN-β) was observed against NDV infection [53,54]. Surprisingly, in our experimental settings, we were unable to observe this response.…”
Section: Discussioncontrasting
confidence: 80%
“…Major genes including IL1β, IL6, IL8, CCL4, CCL5, STAT1, TLR3, IRF7, IFITM-1, IFITM-3, IFITM-5, STAT1, NF-kB, MX1, RSAD2 (viperin), MDA5, and ZAP were identified in this study ( Supplementary Table S1). Interestingly, among all those crucial genes related to innate immunity identified in the present study, we found that TLR3, TLR7, IL1B, IRF7, IL8, STAT1, and MHC class I and II molecules are exactly the same as those observed in previously studies where similar gene expression was shown in CEFs treated with NDV (genotype VII and IX) [53,54]. In short, our results demonstrated a low level (nonsignificant) expression of IFN-α and IFN-β.…”
Section: Kegg Pathway Enrichmentsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, induced pluripotency in chicken eF can generate germ cells and facilitate their optimal survival and migration to embryonic gonads via the chemokine receptor-linked pathway 19,20 . in addition to impacts on egg development, eF can play key roles in the innate immunological recognition and tissue repair following infection and inflammatory insults to the reproductive organs [21][22][23] . in the present study, eFs were used to compare the relative toxicities of inorganic heavy metals, which are known to contaminate mammalian and avian diets as well as drinking water.…”
Section: Introductionmentioning
confidence: 99%